2011
DOI: 10.1016/s2225-4110(16)30059-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot-Attribute Aged Ginger Tea on Chinese Medical Pulse Condition of Healthy Young Humans

Abstract: Young individuals typically have a dry-heat (燥熱 zào rè) constitution and feel overly stimulated. This study observes specialties on the right-bar (右關 yòu guān) section of the radial-arterial pulse of healthy young subjects, and investigates pulse variations induced by different attribute foods. Chinese medical doctors grouped thirty subjects into heat and non-heat constitutions. Each subject took water, aged ginger tea, and coconut water, well recognized as neutral, hot, and cold drinks, on different visits. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These findings also have implications on the choice of the measurement locations in pulse diagnosis spectral studies. It is strongly necessary to put forward the theoretical basis for choosing either inch, bar, cubit [ 3 , 5 , 7 ], pulse ridge [ 8 ], or deeper location [ 39 ]. Stronger theoretical evidence is needed for the chosen location to avoid missing the pulse wave information that is implied at other locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings also have implications on the choice of the measurement locations in pulse diagnosis spectral studies. It is strongly necessary to put forward the theoretical basis for choosing either inch, bar, cubit [ 3 , 5 , 7 ], pulse ridge [ 8 ], or deeper location [ 39 ]. Stronger theoretical evidence is needed for the chosen location to avoid missing the pulse wave information that is implied at other locations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huang et al applied the theory that the left inch reflects the heart to analyze the spectral harmonic energy ratio of each harmonic of the patients with palpitation [ 4 ]. Chao et al applied the theory that the right bar reflects the digestion function to observe the change in the pulse wave of the right bar caused by the hot-attribute aged ginger tea [ 5 ]. The methods used in those studies indicated that different pulse diagnosis locations exhibit the organ-corresponding characteristics or a stronger connection to different organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three studies were conducted in Taiwan, China (Chang and Chen, 2016; Chao et al , 2011; Tseng et al , 2005) three in Iran (Zemestani et al , 2016; Rafraf et al , 2015; Zeraatpishe et al , 2011) and one in Turkey (Akdogan et al , 2007), Japan,(Yui et al , 2017) Canada (Connelly et al , 2014) and the UK (Grant, 2010). Of the ten studies identified, seven were good quality and ranking 3 or higher on the Jadad scale (Table II) (Chang and Chen, 2016; Zemestani et al , 2016; Rafraf et al , 2015; Yui et al , 2017; Connelly et al , 2014; Grant, 2010; Tseng et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…While a growing number of studies have looked at ginger per se in relation to health, few trials have focussed on ginger tea. One study (Chao et al , 2011) found that stroke volume increased and pulse pressure decreased in non-heat constitution subjects (neutral and partial cold body temperature) after drinking 250 ml aged ginger tea compared with baseline, indicating effects on sympathetic activity.…”
Section: Resultsmentioning
confidence: 99%